1996
DOI: 10.1046/j.1365-2575.1996.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Formalized systems development methodologies: a critical perspective

Abstract: Systems development issues occupy a position of central importance in the information systems field and much has been prescribed in the quest for successful systems development. However, given the well‐documented ‘software crisis’, success is far from guaranteed for systems development projects. Many researchers see the solution to the software crisis in terms of increased control and the more widespread adoption of rigorous and formalized system development methodologies. This paper presents some arguments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
116
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(124 citation statements)
references
References 47 publications
7
116
0
1
Order By: Relevance
“…In light of this, it is not surprising that systems development methodologies (SDMs) should be the subject of extensive research. The literature has traditionally viewed them as axiomatically appropriate to improving both the process and product of systems development [20], with their use being typically seen as valuable. While there are a number of significant arguments in their favour, there are also a number of arguments and pressures that question the use of methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this, it is not surprising that systems development methodologies (SDMs) should be the subject of extensive research. The literature has traditionally viewed them as axiomatically appropriate to improving both the process and product of systems development [20], with their use being typically seen as valuable. While there are a number of significant arguments in their favour, there are also a number of arguments and pressures that question the use of methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research shows that method use in practice is rather limited (Fitzgerald 1996;Hidding 1996), and in fact, an empirical study by Fitzgerald (1998) found that only 6 percent of developers rigorously adhere to methods at all. This does not necessarily mean that all of these developers did not duly consider each practice or method before dropping them, but such a scenario is highly unlikely given that adherence is so low.…”
Section: Critical Success Factors For Methods Tailoringmentioning
confidence: 99%
“…A number of methods are included in this family, the most popular being eXtreme Programming (XP) (Beck 1999), the dynamic systems development method (DSDM) (Stapleton 1997), Scrum (Schwaber and Beedle 2002), Crystal (Cockbum 2001), agile modeling (Ambler 2002), feature driven design (Coad et al 1999), and lean software development (LSD) (Poppendieck 2001). These methods represent a popular initiative that complements the critique of formalized ISD methods over the past decade or so (Baskerville et al 1992;Fitzgerald 1994Fitzgerald , 1996, and have been well received by practitioners and academics alike. In fact, after 40 years of research showing that developers rarely adhere to formalized methods (Fitzgerald 1997(Fitzgerald , 1998Hardy et al 1995;Jenkins et al 1984;Necco et al 1987), there is now anecdotal evidence to suggest use of agile methods has been growing rapidly since their inception.…”
Section: Introductionmentioning
confidence: 99%
“…The facility also allowed the employees to voice their satisfaction regarding the different elements of the training. This provided the participants with the opportunity to take part in the ongoing customisation of the training model, and therefore increase the likelihood of user acceptance (Whitten et al, 1994;Fitzgerald, 1996;Bocij et al, 1999).…”
Section: Eet Programmementioning
confidence: 99%